Henry Clay et la South American Question. - Monica Henry (Transatlantica)
In March 1818 the Speaker of the House of Representatives Henry Clay raised the question of recognition of the new Spanish‑American Republics in the House by presenting a resolution making an appropriation for a minister to Buenos Aires. This article argues that beyond the debate that took place in Congress about whether to recognize or not the new governments in Spanish America, what really divided the Representatives was opposing visions of future relations between North and South America in the post‑revolutionary period.